Manajemen diri untuk meningkatkan motivasi belajar pada remaja dengan conduct disorder - Anita Rohman (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
Conduct disorder is a common and  highly destructive psychiatric disorder that  usually  appears in childhood or adolescence and is characterized by severe antisocial  and aggressive behavior.  In this case, the subject  often started physical fights, stole small items without facing a victim, often went out at night even though his parents prohibited him from starting  before  13 years old, often skipped school  starting  before  the age  of 13 years, and behavioral disorders causing significant stress or dysfunction. clinical social aspect. Meanwhile, learning motivation is defined as a process in which goal-directed learning  activities are initiated and maintained. Subjects have  low learning  motivation which is indicated  by the absence of perseverance to do assignments, lack of interest  in learning,  lack of independence to do assignments, lack of appreciation in learning, and  lack of confidence and  pleasure in solving problems in lessons. The  assessment methods used were  interviews, observation, Wechsler Adult Intelligence Scale (WAIS), graphic tests (DAP, BAUM, HTP), Saks Sentence  Completion Test  (SSCT), and  self reports. The intervention used is self management. The result of the intervention is that the subject  has  been  able to improve the behavior  of doing the task from 0 times  to 3 times  in one  week.  Subjects were  also  able  to reduce the intensity  and  duration  of excessive play behavior from 4 times a week with a duration  of more  than 6 hours  per day, to 2 times a week with a duration  of 2-4 hours  per day.